Analisis Implementasi SIMRS Registrasi Rawat Jalan dan UGD Metode HOT-FIT di RSU Penyangga Perbatasan Betun - Benedicta Cherlyn Pera; Maya Weka Santi; Atma Deharja; Mudafiq Riyan Pratama (Indonesian Journal Publisher, 2025)
RSUPP Betun in Malaka Regency began implementing the Hospital Management Information System (HMIS) in June 2021 to support outpatient and emergency department (ED) registration. A preliminary study identified several issues, including a lack of staff training, technical disruptions with hardware and software, and network instability. This study aims to analyze the implementation of HMIS in the Outpatient Registration and ED units at RSUPP Betun using the HOT-FIT method. The research is qualitative, using interviews, observations, and documentation for data collection. The study's informants included seven individuals: the head of the medical records department, five registration staff, and one IT staff member. The results indicated that training improved user knowledge, but additional features, such as an alert system, are still required. Organizational support, funding, and inter-unit communication had a positive impact. However, the technological aspect revealed the need for better technical guidelines and higher-quality information. IT services were responsive, but the limited human resources hindered HMIS maintenance. Overall, HMIS has not yet fully improved service effectiveness due to suboptimal data integration. Recommendations include regular training, technical guidelines, a helpdesk feature, automatic logout, and SIMRS infrastructure updates.